Study on Collection and Utilisation of Minor Forest Produces by Mountain Women - De, Sejuti Sarkar (Indian Forester, 2017)
The study was conducted on 107 women villagers of four villages at Dhanaulti in Uttarakhand, India for qualitative and quantitative measurement of collection and utilisation of Minor Forest Produces (MFP) by women. Mountain women regularly collect fuelwood, fodder grass, leaves and vegetables, fruits and flowers, medicinal plants and branches from forest. The study reveals that 100% women collect fuelwood and fodder grass round the year except for three months of rain and snowfall. More than 70% women collect 400-600 kg of fuelwood per head annually. About 50% women collect same amount of fodder grass per head annually. 37.38% women collect seasonal leaves and vegetables like Lengra (Diplazium species), Hisar (Rubus duthieanus) etc. and 75.7% women collect fruits and flowers like Bhamor (Cornus capitata), Buransh (Rhododendron) etc. mainly for household consumption. 35% respondents collect more than 80 kg of branches per head annually. Less than 1% women collect medicinal herbs like Chirayta (Swertia chirayita), Satavar (Asparagus recemosus) and Daruhaldi (Berberis aristata). 43.92% of women lack knowledge of collection, processing and marketing of minor forest produces. This is the main reason for not being able to use MFPs commercially. The project conducted trainings on MFP processing and marketing to support income generation for mountain women.